Incidence, Risk Factors, and Outcomes of Cancer in Systemic Sclerosis. Issue 11 (29th October 2020) - Morrisroe, Kathleen; Hansen, Dylan; Huq, Molla; Stevens, Wendy; Sahhar, Joanne; Ngian, Gene‐Siew; Ferdowsi, Nava; Hill, Catherine; Roddy, Janet; Walker, Jennifer; Proudman, Susanna; Nikpour, Mandana
Abstract : Objective: To quantify the burden of cancer in systemic sclerosis (SSc). Methods: Standardized incidence ratios (SIRs) and standardized mortality ratios relative to the general Australian population were derived. Cox proportional hazards regression was used to estimate survival in patients with SSc with cancer compared to patients without. Determinants of cancer were identified using logistic regression. Health care cost was quantified through cross‐jurisdictional data linkage. Results: This SSc cohort of 1, 727 had a cancer incidence of 1.3% per year and a prevalence of 14.2%, with a SIR of 2.15 (95% confidence interval [95% CI] 1.84–2.49). The most common cancers were breast, melanoma, hematologic, and lung. Anti–RNA polymerase III (RNAP) antibody was associated with an increased risk of cancer (odds ratio [OR] 2.9, P = 0.044), diagnosed within 5 years of SSc disease onset. Calcium channel blockers were associated with a higher risk of overall cancer (OR 1.47, P = 0.016), breast cancer (OR 1.61, P = 0.051), and melanoma (OR 2.01, P = 0.042). Interstitial lung disease (ILD) was associated with lung cancer (OR 2.83, P = 0.031). Incident SSc cancer patients had >2‐fold increased mortality compared to patients with SSc without cancer (hazard ratio 2.85 [95% CI 1.51–5.37], P = 0.001). Patients with SSc and cancer utilized more health care than those without cancer, with an excess annual health care cost of 1, 496 Australian ( P < 0.001). Conclusion: SSc carries an increased risk of developing cancer, particularly lung cancer associated with ILD, and breast cancer and melanoma occurring close to SSc disease onset in association with RNAP antibodies. Compared to those patients without cancer, patients with SSc and cancer had higher mortality and an increased health care cost, with an annual excess per patient cost of 1, 496 Australian ( P < 0.001).